Analysis of time and cost using time cost trade off method in pressure vessel project - Rina Sandora; Sri Puji Lestari (UNIPA PRESS, 2023)
One of the construction companies got a Pressure Vessel project job. During the process of working on the project, it was delayed from the predetermined date so that the company had to pay a fine of 0.2% every day. So it is necessary to analyze project scheduling in order to get the optimal time and cost of working on this project. The methods used in this research are Time Cost Trade Off (TCTO), Precedence Diagram Method (PDM) and crashing. Acceleration is carried out on all critical paths contained in fabrication activities. This study uses alternatives to accelerate the addition of 50% and 75% labor. The results of this study obtained the optimal time and cost with the alternative of adding 75% labor. The resulting acceleration duration is 75 days faster than the actual duration, with costs incurred of Rp. 161,386,836, -, resulting in a 56% decrease from the actual duration cost of Rp. 286,961,745, -. Analysis of the S-curve found that the accelerated duration can be completed faster than the actual duration because, the curve line on the accelerated duration is more sloping closer to the y-axis indicating greater progress each week.